The Impact of Digital Competence and Innovative Organizational Culture on Innovative Performance in Indonesian Public Sector - Rati Pundissing; Randi Tangdialla; Ade Lisa Matasik (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Digital transformation is critical for local governments like Tana Toraja Regency, where limited infrastructure and bureaucratic challenges hinder public service innovation. This study aims to examine how digital competence and innovative organizational culture influence the innovative performance of civil servants. The research used a quantitative approach with an explanatory correlational design, collecting data from 365 civil servants in Tana Toraja through proportionate stratified random sampling. Questionnaires measured digital competence, innovative organizational culture, and innovative performance. Data were analyzed using Structural Equation Modeling–Partial Least Squares. The findings show that digital competence strongly enhances innovative organizational culture (path coefficient 0.63) and innovative performance (path coefficient 0.41), while innovative organizational culture boosts innovative performance (path coefficient 0.46), explaining 57% of its variance. These results, significant at p less than 0.001, highlight the importance of digital skills and a supportive culture in driving innovation. The study, limited to Tana Toraja, offers a strategic human resource management model to improve digital literacy and foster an innovative culture, providing policy recommendations for local governments to enhance public services despite regional constraints.